Khrōngkān songs̄œm sētthakit ph̨ōphīang læ prachākhom Čhangwat Krabī, Ran̨ōng, Phangngā læ Phūket : rāingān chabap sombūn (Sathāban Chumchon Th̨ōngthin Phatthanā, 1998)
Report on the sufficient economy promotion and provincial civil society project of Krabi, Ranong, Phangnga and Phuket provinces.